319 CAN INDEX BARTHEL SCORE AT EMERGENCY DEPARTMENT PRESENTATION PREDICT ADVERSE OUTCOMES AMONG OLDER ADULTS AT 30 DAYS AND 6 MONTHS?. (25th October 2022) - Corey, G; Leahy, A; Carroll, I; Barry, L; Galvin, R
Abstract: Background: Frailty is acknowledged as a significant syndrome particularly in the older population. Monitoring frailty in late life aetiology and recognising the value of frailty as a marker of risk for adverse health outcomes is vital and ensures the identification of opportunities for intervention with this cohort in clinical practice. The aim of this prospective cohort study is to examine if an index Barthel Score at Emergency Department presentation predicts adverse outcomes among older adults at 30 days and 6 months. Methods: Six-hundred and fifty older adults (≥65 years) attending a university model 4 hospital ED were recruited. Baseline evaluation included the Barthel Index. Adverse outcomes (hospital readmission or death) were recorded by a research nurse at 30 days and 6 months, blinded to Barthel score. Descriptive statistics were used to profile the population and report the incidence of adverse outcomes. Results: At 30 days, 61 older adults had either being admitted to hospital (n=28) or died (n=33) and at 180 days a further 72 had been admitted (n=43) or died (n=29). A total of 29% (n=189) of the population had a Barthel score of ≤15 indicating moderate dependency. Of this cohort, 70% had an adverse outcome-readmitted or died within 180 days. Conclusion: It may be worth looking at introducing the Barthel Index as a routine measure of activity for older adults presenting to the ED. This tool demonstrates an increased risk of adverse outcomes among older adults who present with moderate dependency. Early intervention either in the hospital or community setting with this 'at risk' cohort may serve to reduce adverse outcomes among this group.